Analysis of Incomplete Filling Defect for Injection-Molded Air Cleaner Cover Using Moldflow Simulation. (7th July 2013) - Shin, Hyeyoung; Park, Eun-Soo
Abstract : A large-sized cover part for air cleaner was injection molded with ABS resin, and its incomplete filling defect was analyzed using commercial Moldflow software. To investigate the effect of processing temperature on incomplete filling defect, tensile properties, weight loss, and phase separation behavior of ABS resin were evaluated. The tensile properties of dumbbell samples were not changed up to 250°C and decreased significantly thereafter. SEM micrographs indicated no significant changes in the status of polybutadiene rubber phase below 250°C. These different test results indicated that ABS resin little affected the thermal decomposition in processing temperature range. The Moldflow simulation was performed using measured thickness of molded cover and actual mold design with the defects. As expected, the cover part showed unbalanced filling and incomplete sections. To improve these defects, two possible cases of hot runner system have been simulated. When applying modified 5-gate system, the maximum injection pressure was decreased approximately 5.5% more than that of actual gate system. In case of 6-gate system, the maximum injection pressure reduced by 23%, and the injection pressure required to fill is well within the range of the molding equipment. The maximum clamping force of 6-gate system was also significantly reduced than that of actual and 5-gate system.